PEMBANGUNAN SISTEM INFORMASI KEHADIRAN SISWA BERBASIS RFID PADA SMK INFORMATIKA PELITA NUSANTARA - Dedi Juniansha; Ramdani Budiman (Jurnal Ilmiah Sains dan Teknologi, 2020)
This study presents the use of radio identification system with integrated active antenna technology on student attendance system. We describe RFID technology as a clever way to transmit data via radio and by using the function of Active Integrated Antennas (AIA) RFID as a way of receiving and sending. RFID technology can be used as a replacement or improvement of technology the item code (barcode) without visibility. Students are terpeting component in education, to manage and control the students is a must to make the institution as a place of discipline Hammersmith. By making information systems student attendance will help other systems such kuangan systems, assessment systems and other systems. Research on the use of RFID technology the student attendance system using the method of analysis, design and literature. Results that will be achieved is how merancangang a student attendance system automatically using RFID technology, merancangan a student attendance application that can overcome the problems encountered and prove the accuracy of the technologies of RFID.